“They can’t even agree!” Student conversations about their supervisors in constructing understandings of the PhD - Akala, Benard; Backhouse, Judy (South African Journal of Higher Education, 2016)
This paper examines conversations among doctoral students about their supervision experiences. It is a foray into their spare time, when they reflect through conversations, on encounters with their supervisors. While these conversations are usually stimulated by gossip around lifestyles, entertainment and frustration, they represent useful generative spaces for negotiating meaning around the complexities of doctoral supervision. We argue that, if student conversations are stimulated as critical spaces for engagement, where shared meaning about supervision experiences is discussed, they can promote effective student/supervisor interaction and enhance learning. This is to generate a debate that can turn student contestation over doctoral supervision into generative and productive mechanism for understanding the nature of such supervision. The data was collected using ethnographic strategies in the form of notes recorded by students at Wits and UJ.